Development and evaluation of training in culturally specific screening and brief intervention for hospital patients with alcohol‐related injuries. (19th May 2015) - Whitty, Megan; Nagel, Tricia; Jayaraj, Rama; Kavanagh, David
Abstract: Objective: To evaluate health practitioners' confidence and knowledge of alcohol screening, brief intervention and referral after training in a culturally adapted intervention on alcohol misuse and well‐being issues for trauma patients. Design: Mixed methods, involving semi‐structured interviews at baseline and a post‐workshop questionnaire. Setting: Targeted acute care within a remote area major tertiary referral hospital. Participants: Ten key informants and 69 questionnaire respondents from relevant community services and hospital‐based health care professionals. Intervention: Screening and brief intervention training workshops and resources for 59 hospital staff. Main outcome measures: Self‐reported staff knowledge of alcohol screening, brief intervention and referral, and satisfaction with workshop content and format. Results: After training, 44% of participants reported being motivated to implement alcohol screening and intervention. Satisfaction with training was high, and most participants reported that their knowledge of screening and brief intervention was improved. Conclusion: Targeted educational interventions can improve the knowledge and confidence of inpatient staff who manage patients at high risk of alcohol use disorder. Further research is needed to determine the duration of the effect and influence on practice behaviour. Ongoing integrated training, linked with systemic support and established quality improvement processes, is required to facilitate sustained change and widespread dissemination.